Adherence to Levothyroxine Treatment Among Patients With Hypothyroidism: A Northeastern Italian Survey - Cappelli, Carlo; Castello, Roberto; Marini, Fiorella; Paoletta, Agostino; Marchetti, Massimo; Saullo, Maura; Cristiano, Alessandra; Pirola, Ilenia; Gandossi, Elena; Ferlin, Alberto; Castellano, Maurizio (Frontiers in Endocrinology, 2018)
Background: A significant number of patients show sub-optimal adherence to levothyroxine (LT4) therapy, mainly because they have to postpone their breakfast by at least 30 min. The aim of this observational cross-sectional study was to assess the therapeutic compliance of patients on LT4 treatment and to verify the preference of a lifetime treatment in tablet or liquid form. Patients and Methods: Ambulatory care patients aged 18 years or older, affected by hypothyroidism and on LT4 treatment (in tablet or liquid form) were administered the eight-item Morisky Medication Adherence Scale (MMAS-8). The MMAS-8 questionnaire was supplemented with 3 further items to specifically evaluate preference between tablet and liquid forms of LT4 for lifetime treatment. Results: A total of 320 patients (272 female), median age 47.9 ± 15.6 years (range, 20–78 years), completed the MMAS-8 questionnaire. Eighty-seven percent of the participants were adhering to their treatment for both tablet and liquid LT4 formulations, although significant differences emerged. Patients on LT4 tablets forgot to take their medication more frequently (p < 0.001), felt hassled about sticking to their treatment plan (p < 0.001), and had difficulty remembering to take all their medication(s) (p < 0.001) than those on liquid LT4 treatment. Conclusions: Adherence to LT4 treatment was high for both tablet and liquid formulations. Taking LT4 at breakfast was the most convenient option for most patients.